Employee Performance is Assessed in Terms of Motivation, Compensation, Work Environment, and Career Development - Novita Krisnasari; Istiatin Istiatin; Siti Maryam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of motivation, compensation, work environment, and career development on employee performance in Serengan District, Surakarta City. The research method used is a quantitative approach with data collection techniques through questionnaires distributed to 40 respondents who are State Civil Apparatus (ASN) in Serengan District. Data analysis techniques used include classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficient of determination (R²) with the help of the SPSS 26.00 for windows program. The results of the study indicate that all independent variables, namely motivation, compensation, work environment, and career development, have a positive and significant effect on employee performance, both partially and simultaneously. The compensation variable has the most dominant influence on employee performance. The results of the coefficient of determination test show that 53.7% of employee performance variations can be explained by these four variables, while the remaining 46.3% is influenced by other variables outside this study. Increasing motivation, providing appropriate compensation, a conducive work environment, and targeted career development can improve employee performance in Serengan District, Surakarta City.